ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN MELAKUKAN PEMBELIAN RUMAH PADAPERUMAHAN ARUM LESTARI DI BANDAR LAMPUNG - Jeny Puspita (SOSIALITA, 2018)
THE ANALYSIS OF FACTORS AFFECTING DECISION CONSUMERS BUY THE HOUSE BY HOUSING ARUM LESTARI IN BANDAR LAMPUNG The purpuse of this research is to know and analyze how big a factor the price, the location, building, the environment affect consumers in the buying the house on an estate arum lestari bandar lampung. This study using samples from 35people of respondent that is the housing arum lestari lampung.In the methode do applying for collecting data by documentation study, observation and interview, and then the angket. For processing data using the multiple regression analysis to know relation indefendent variable (X1) Price, (X2)Location, (X3)Building, and (X4)Environment to influence defendant variable (Y) Purchase Decision. Furthermore in its data analysis using SPSS Statistics 18 program. The results of these research appeared that by significant 0,05 for two side test 2,5% and n =35 to obtain t statistics’s table 2,04227. But t from testing 2,570 for price;2,898 for location; 2,610 for building; and 2,688 for environment therefore price, location, building and environmenthas positive significant influences to purchase decision at people of respondent that is the housing arum lestari Lampung.